IMPLEMENTASI LESSON STUDY MELALUI MODEL PEMBELAJARAN KOOPERATIF TEAM GAMES TOURNAMENT (TGT) PADA MAHASISWA PRODI PBSI STKIP MUHAMMADIYAH KOTABUMI - Windo Dicky Irawan (Edukasi Lingua Sastra, 2018)
This research is a qualitative descriptive research that aims to describe what it is about the activities of students study program in General Linguistics learning. Data collection is done by using planning stages (plan), implementation (do), and reflection (see) that focus on student activities. The subjects of this study are students of first semester of class A of PBSI study program. What is observed is the increase in student activity on each cycle. The research process is carried out with several stages: (a) conducting observations of research subjects, (b) performing data retrieval, (c) analyzing data on each cycle, (d) conducting discussion of the results of the analysis, (e) drawing conclusions of research results. The results showed that: 1) the implementation of learning through cooperative model Team Games Tournament can increase the activity, enthusiasm of students, 2) the implementation of learning with cooperative model Team Games Tournament can improve student ability.